International Cooperation in Preventing Tax Evasion - Rzetecki, Adam (Journal of Finance and Financial Law, 2018)
Free movement of people, goods and services, and capital within the EU challenges for member states' authorities because of the risk of avoiding tax payment by citizens and companies. The article describes legal regulations concerning the cooperation between the sates' authorities in relation to exchange of tax relevant information, not only on national but also on international level. The main purpose of this article is to present the importance of information exchange in tax matters with foreign tax authorities in the context of the transfer of profits to tax havens.